Patient and Caregiver Needs in Oncology. An Italian Survey. Issue 6 (November 2015) - Berardi, Rossana; Ballatore, Zelmira; Bacelli, Weruska; Silva, Rosa Rita; Menichetti, Ettore Tito; Marcellini, Massimo; Duca, Monia; Giacomini, Giusi; Marilungo, Katia; Cascinu, Stefano
Aims and Background: Cancer is a disease that has far-reaching consequences for patients and their families. The present study targets unmet caregiver needs so that better support can be provided and planned for. Methods: The first phase of the study was to conduct a survey designed to explore basic needs (medical and nursing information, psychological support, social welfare). The survey also investigated the caregiver's personal details (age, sex, degree of kinship). The survey was distributed to caregivers coming to the day hospitals of the 4 oncology departments involved in the study. Results: A total of 137 relatives of cancer patients completed the survey. Among the explored needs, the most recurrent was the availability of a doctor who provides full information on the treatment choices. A further important request was for consistency between the information provided by doctors and that provided by other health-care workers, with specific reference to a patient-centered approach that can be easily and fully understood, available therapeutic options especially at home, and prognosis. Conclusions: The study showed that the need for exhaustive and simple information provided by a referral physician is still an unmet need in the Internet age.